THE ECLIPSING BINARY SYSTEM BM ORI - Bondar', N. I.; Vitrichenko, E. A (Одеські астрономічні публікації, 2017)
Photometric and spectroscopic features of eclipsing binary system BM Ori can be described well by a model in which the components are the primary star B3 ZAMS, the secondary F2 pre-main sequence star and a dusty envelope of large grains around the secondary. The eclipse on ingress and egress phases has been produced by a dust envelope only, but during the total phase the F2 star makes yet the partial eclipse. Eclipsing binaries in which the major puzzle is a nature of an eclipsing body are considered. Some parameters indicate that candidates to relative objects to BM Ori can be ε Aur, TY CrA, ϑ1 Ori A and variable stars in multiple systems.